Assistance in Developing a Merchandise Inventory Recording and Calculation System for the MSME Toko Fahry Wijaya - Wahyuni; Masrullah; Armansyah Hilman; Muh Syamrialdi F.S; Muhammad Yasser; Asrar Abukair; Anugrah Ramadhan; Sudirman (Masterpiece, 2026)
Micro, Small, and Medium Enterprises (MSMEs) contribute significantly to national economic growth. However, many MSME operators still face challenges in managing merchandise inventory, particularly regarding record-keeping and stock control systems. This situation applies to Toko Fahry Wijaya, an MSME specializing in the sale of Muslim clothing and fashion accessories. This community service initiative aimed to provide guidance on establishing a system for recording and calculating merchandise inventory by implementing a periodic inventory system using the First-In, First-Out (FIFO) method. The activity was carried out in several stages: observation, problem identification, initial inventory data collection, development of inventory recording formats, socialization, training, mentoring, and evaluation. The program took place from June 14 to June 24, 2026, at Toko Fahry Wijaya in Makassar City. The results indicate that the business partner has gained an understanding of the importance of structured inventory recording, the use of stock cards for inventory control, and the calculation of ending inventory using the FIFO method. The implemented recording system also assists the business owner in more effectively monitoring the inflow and outflow of goods. Consequently, this initiative successfully enhanced the partner's inventory management capabilities, thereby supporting the preparation of more accurate financial reports and facilitating better business decision-making.